Phragmipedium humboldtii (Warsz.) J.T. Atwood & Dressler: on the correct name for the Central American long-petaled Phragmipedium; again - Pupulin, Franco (2016)
I was quite convinced that the complicated taxonomic history of the Central American long-petaled Phragmipedium, which has been misunderstood for over a century and caused a lot of uncertainties among both professional botanists and horticulturists, had finally been clarified in a rather technical paper I published along with Bob Dressler some years ago (Pupulin and Dressler 2011). This supposition must have been wrong, though, as at least three papers aimed at rediscussing the nomenclatural status of Phragmipedium humboldtii (Warsz.) J.T. Atwood & Dressler have been published recently (Braem 2014a, 2014b, 2015), contributing, I fear, to revamping ambiguities and confusion about the correct name to be used for this beautiful Phragmipedium from the Central American isthmus. More concerns arise, however, from the number of students, herbarium curators and amateurs who contact me trying to disentangle the confusion of the past and put a correct name to both living and dry specimens of Phragmipedium.